Simultaneous quantification of B-complex vitamins in tablet dosage form by ultraviolet spectrophotometry using the absorption factor method - Effendy De Lux Putra; Siti Morin Sinaga; Harfiansyah, M. Deddy (Faculty of Science and Technology, Universitas Islam Negeri Walisongo Semarang, 2025)
A novel ultraviolet (UV) spectrophotometric method using the absorption factor approach was developed for the simultaneous quantification of B-complex vitamins (cobalamin, pyridoxine, riboflavin, nicotinamide, and thiamine) in tablet dosage forms. The analysis was carried out using methanol as the solvent, with distinct wavelengths selected for each vitamin: 361 nm for cobalamin, 291 nm for pyridoxine, 269 nm for riboflavin, 262 nm for nicotinamide, and 239 nm for thiamine. The method exhibited excellent accuracy, with recovery rates of 100.0851%, 100.3548%, 100.3322%, 100.7838%, and 100.4271% for cobalamin, pyridoxine, riboflavin, nicotinamide, and thiamine, respectively. This technique provides a simple, precise, and effective means for simultaneous quantification of B-complex vitamins in tablet formulations. The method satisfies all validation criteria and shows minimal interference from excipients, making it a reliable tool for quality control in pharmaceutical analysis.